Identification of airborne radioactive spatial patterns in Europe – Feasibility study using Beryllium-7. (May 2016) - Hernández-Ceballos, M.A.; Cinelli, G.; Tollefsen, T.; Marín-Ferrer, M.
Abstract: The present study proposes a methodology to identify spatial patterns in airborne radioactive particles in Europe. The methodology is based on transforming the activity concentrations in the set of stations for each month (monthly index), due to the tightly spaced sampling intervals (daily to monthly), in combination with hierarchical and non-hierarchical clustering approaches, due to the lack of a priori knowledge of the number of clusters to be created. Three different hierarchical cluster methodologies are explored to set the optimal number of clusters necessary to initialize the non-hierarchical one (k-means). To evaluate this methodology, cosmogenic beryllium-7 ( 7 Be) data, collected between 2007 and 2010 at 19 sampling stations in European Union (EU) countries and stored in the Radioactivity Environmental Monitoring (REM) database, are used. This methodology yields a solution with three distinguishable clusters (south, central and north), each with a different evolution of the 7 Be monthly index. Clear differences between monthly indices are shown in both intensity and time trends, following a latitudinal distribution of the sampling stations. This cluster result is evaluated performing ANOVA analysis, considering the original 7 Be activity concentrations grouped in each cluster. The statistical results (among clusters and sampling stations within clusters) confirm the spatial distribution of 7 Be in Europe, and, hence, reinforce the use of this methodology. Finally, the impact of tropopause height on this grouping is successfully tested, suggesting its influence on the spatial distribution of 7 Be in Europe. For airborne radioactive particles the analysis gave valuable results that improve knowledge of these atmospheric compounds in Europe. Hence, this work addresses a methodology to a grouping of airborne sampling stations, 1) allowing a better understanding of the distribution of 7 Be activity concentrations in the EU, and 2) serving as a basis for further investigation of the heterogeneity of airborne radioactivity concentrations in Europe. Highlights: Methodology to identify spatial patterns in airborne radioactive particles. Methodology combining the monthly index and cluster methods. Validation of the methodology using 7 Be in Europe. Identification and validation of temporal patterns of 7 Be in Europe. Positive impact of tropopause height on spatial distribution of 7 Be concentrations.